A Production operations management study on Four Dimension Sleep Products Manufacturing Corporation - Dy, Glady G. (College of Engineering, 2003)
The project site is Four Dimension Sleep Products Manufacturing Corporation, a manufacturing company in Pasig City. The organization manages a production system that produces a diverse selection of mattresses and pillows regularly and distributes sleep products to numerous malls in the country. The key interests of the report are the design and processes employed for the assembly of products, the management of workforce and supply chain, and capacity planning. Subsequently, the study looks into other production planning concenrs such as inventory management and scheduling. Plant visits were conducted during the months of January and February of year 2003. Relevant data such as the history and organizational background of the company, systems and procedures in the production department, and operation times were obtained from interviews, observations and time study. The group only focused on current procedures of the manufacture of mattresses and pillows which are regarded as top 80% of 4d's products based on unit sales (using Pareto Chart). The products of interest are illustrated thoroughly by the presentation and discussion concerning its design, dimensions, and quality characteristics. The manufacturing process was documented with the use of a process map. This was further summarized into a process flow chart diagram. Detailed discussions, computations, and analysis on the plant layout, capacity and utilization, forecasting technique, and production planning are also incorporated in the system documentation. Histograms are also constructed (for inventory management) and the results are interpreted. The Areas of Concern are identified and the problems are disclosed, verified and evaluated. The tool applied for this stage is the Streamline Diagnosis Analysis. The three major problems that surfaced are: lack of a reliable forecasting technique, poor raw material inventory management, and unforeseen overtime. The group suggested an appropriate forecasting approaches and performed error analysis with each. To determine if the present workforce is capable of meeting the forecasted demands, and thus make production decisions, four strategies are generated and evaluated for total costs. An efficient and systematic inventory management system that minimizes inventory costs was recommended as well. Another problem - plant layout - was addressed by illustrating a new arrangement of the working areas within the plant. The enhanced flow for each department was also shown. Distances traveled to and from subsequent operations are reevaluated and improvements resulted. After examining the documentation for both products and the processes, along with the problem analysis, alternatives were generated using brainstorming. The alternatives were then evaluated using criteria given by the management. The group also performed a comprehensive analysis of the production and proposed a set of alternative strategies to improve inspection and process capability in the plant. Appropriate conclusions and implementation guidelines were formulated to address the identified problems and meet the specific objectives stated, which are consistent with the mission of the company.